Influence of basement fabrics on fault reactivation during rifting and inversion: a case study from the Celtic Sea basins, offshore Ireland. Issue 1 (2023) - Rodríguez-Salgado, P.; Childs, C.; Shannon, P. M.; Walsh, J. J.
No abstract available